Occurence of trichodinid ciliates (Peritricha: Urceo-lariidae) in the Kiel Fjord, Baltic Sea, and its possible use as biological indicator - Palm, Harry; Dobberstein, R. C. (Parasitology Research, 1999)
Investigations on the occurrence of trichodinid ciliates from fish caught in the Kiel Bight and Kiel Fjord (western Baltic Sea) were carried out between September 1996 and March 1997. Smears of the gills, fins, and skin of 120 Gadus morhua and 92 Platichthys flesus caught by fish traps and trammel nets revealed the presence of trichodinid ciliates. According to the fish species and locality, different prevalences and densities of trichodinid ciliates were found. Fish caught in the Kiel Bight revealed a lower prevalence of trichodinid ciliates on their gills (P. flesus 74.2%, G. morhua 3.8%) in comparison with fish of the same species and size caught in the Kiel Fjord (P. flesus 75.0%, G. morhua 26.2%). In both areas, P. flesus was more heavily infested than G. morhua. Seasonal changes in the prevalence of infestation of P. flesus between autumn and winter in the Kiel Fjord are proposed to be linked to an increase in bacterial biomass during winter. The fish ecology in combination with the total number of bacteria in the fish environment is discussed as an important factor influencing the abundance of trichodinid ciliates. The present data suggest the use of trichodinid ciliates as an indicator for eutrophication in brackish-water environments.